THE UTILIZATION OF ALTERNATIVE THERAPIES IN PAIN CONTROL BY NURSES - Ghroop Yahia Ahmad Mobtti , Khalid Safaq Swait Alenezi , Layan Ayed Alamri , Khulood Eissa Aswani , Huda Misaeed Alrhaily , Khaled Matoog Algashmari , Emad Faisal Shabander , Qubyl Nasser Al-Saran ,Rasha Yati Othman Alkhaibari , Ageela Mohmed Mosa Safhi,,; Shagra Saeed Albashr , Salman Raja Al-Sahli, Halah Rashed Aldosari , Randa Najeeb Almasoud , Mohammed Yahya Abdullah Fagih , Fatimah Abdrabali Albahlool , Fullah Ahmed Alhamali, (Chelonian Research Foundation, 2022)
Severe discomfort is regarded as one of the most distressing recollections among those who are really sick. Nevertheless, the pain experienced by these individuals is not well addressed owing to many obstacles that hinder the implementation of appropriate treatment. Hence, it is essential to tackle the perceived obstacles and enablers to pain assessment management among critical care nurses. The obstacles and facilitators were classified into four distinct categories: nurse-related, patient-related, physician-related, and system-related. The primary obstacles identified in this study were nurses' insufficient understanding of pain assessment tools, patients' inability to communicate, physicians' prescribing analgesics without considering pain scores, and the absence of standardized guidelines and protocols for pain evaluation and management. The most commonly reported facilitators for pain assessment and management include continuous education and professional training, patients' capacity to self-report pain, efficient collaboration between physicians and nurses, and meaningful discussion of patients' pain scores during nurse-to-nurse handovers. This study identified and investigated many obstacles and factors that either hinder or assist in the evaluation and treatment of pain. Nevertheless, further study is required to thoroughly explore these obstacles and enablers, as well as to scrutinize any other possible related aspects among critical care nurses. The results of our research should assist hospital administrators in creating ongoing education and professional development initiatives focused on evaluating and addressing pain in critically ill patients. Furthermore, our discoveries might be used to create a scientifically supported pain management approach that is customized to accurately evaluate and swiftly address pain in patients receiving critical care. Keywords: critical care nurses, pain assessment, pain treatment, obstacles, facilitators, supporters, difficulties.